The cult of Theoi: Economic uncertainty and religion - Paul Frijters; Juan D. Barón (Institute for the Study of Labor (IZA), 2010)
Sacrifices to deities occur in nearly all known religions. In this paper, we report on our attempts to elicit this type of religious behaviour towards Theoi in the laboratory. The theory we test is that, when faced with uncertainty, individuals attempt to engage in a reciprocal contract with the source of uncertainty by sacrificing towards it. In our experiments, we create the situation whereby individuals face an uncertain economic payback due to Theoi and we allow participants to sacrifice towards this entity. Aggregate sacrifices amongst participants are over 30% of all takings, increase with the level of humanistic labelling of Theoi and decrease when participants share information or when the level of uncertainty is lower. The findings imply that under circumstances of high uncertainty people are willing to sacrifice large portions of their income even when this has no discernable effect on outcomes.
Keywords: D8; Z12; 330; Uncertainty; religion; sacrifice; experiment; Religion; Spende; Risiko; Verhaltensökonomik; Test